A narrative review: Risk factors of low back pain in military personnel/recruits - Waqqash, Ebby; Hafiz, Eliza; Hamid, Mohamad Shariff A.; Nadzalan, Ali Md (Science Publishing Corporation, 2018)
Military personnel are one of the occupations at high risk of developing low back pain (LBP) due to its job demands. Low back pain (LBP) is a major cause of morbidity and lost from work among military personnel. This narrative review was conducted to determine the risk factors of LBP in military personnel/recruits. Searches focusing on causal comparative and epidemiology studies using OVIDMedline, CINAHL, SPORTDiscus, PubMed, and Scopus databases from year January 1950 to April 2018. The Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines was used to select and synthesis of studies. The strongest personal risk factors identified were history of LBP (OR = 8.91, CI = 1.71 -46.5), female gender (OR: 6.59, CI 1.79 - 24.24), aerobic exercise involvement (OR = 4.39, CI 1.53- 12.57) and older age (OR 4.16). The strongest occupational risk factors identified were pro-longed hours of flight per day (OR=11.3, CI 5.2 -24.8), driving in forward bending posture (OR = 3.63, CI 1.06 - 12.42), branch of services (Army; OR 2.74, CI 2.60-2.89 & Air Force; 1.98, CI 1.84 -2.14), Night training (OR = 1.8-2.0, CI 1.1 - 3.1) and whole-body vibra-tion exposure (OR 1.94, CI 1.02 -3.69). The strongest psychosocial risk factors identified were worries (OR = 5.47, CI 1.70- 17.62), no support from others (OR = 4.0, CI 1.31 -12.34) high work stress (OR = 3.47, CI 1.31 - 12.34), depression (OR = 1.75, CI 1.08 -2.83), and psychological stress (OR 1.71). This review summarizes the personal, occupational and psychosocial risk factors associated with LBP among military personnel/ recruits. LBP risk factors differs based on the military branch of services and job scope. Primary LBP risk factor for Air Force pilots, helicopter pilots and military vehicle drivers LBP is sitting ergonomics. Primary LBP risk factor for army (i.e. combat infantry) identified are occupational physical exposure (military training, heavy lifting and carrying, patrol durations.) Further studies are required to verify if there is any interaction between personal, occupational, and psychosocial LBP risk factor categories among military personnel/recruits.